Basic Determinant of the Success of Interpersonal Relationship: Rejection Sensitivity - Dilek Sirvanli Ozen; Fulya Kubra Güneri (Psikiyatride Güncel Yaklaşımlar, 2018)
The rejection sensitivity, which is defined as waiting to be rejected, being ready to perceive, and being overreacted to rejection, is seen as an important fact affecting the social and psychological adjustment of the individual, the interpersonal relationship. The relevant literature, which states that the rejection sensitivity has a cognitive-affective processing dynamic, sees it as an advocacy motivational system intended to protect the possible rejection of the self from possible other people. On the other hand, the most important source of rejection sensitivity is parents, and in this context, they are closely related to attachment and parenting styles; at the same time it is stated that the rejection sensitivity is related to some psychopathologies and that most people affect romantic relations. Moving from these points, the purpose of the study is guiding the possible empirical work to be done in the future for the rejection sensitivity which is in the focus of the interpersonal relationship success.